The Microbiota in Systemic Lupus Erythematosus: An Update on the Potential Function of Probiotics - Guo, Xirui; Yang, Xuerong; Li, Qi; Shen, Xiaoyan; Zhong, Huiyun; Yang, Yong (Frontiers in Pharmacology, 2021)
Systemic lupus erythematosus (SLE) is a kind of chronic diffuse connective tissue illness characterized by multisystem and multiorgan involvement, repeated recurrence and remission, and the presence of a large pool of autoantibodies in the body. Although the exact cause of SLE is not thoroughly revealed, accumulating evidence has manifested that intake of probiotics alters the composition of the gut microbiome, regulating the immunomodulatory and inflammatory response, which may be linked to the disease pathogenesis. Particularly, documented experiments demonstrated that SLE patients have remarkable changes in gut microbiota compared to healthy controls, indicating that the alteration of microbiota may be implicated in different phases of SLE. In this review, the alteration of microbiota in the development of SLE is summarized, and the mechanism of intestinal microbiota on the progression of immune and inflammatory responses in SLE is also discussed. Due to limited reports on the effects of probiotics supplementation in SLE patients, we emphasize advancements made in the last few years on the function and mechanisms of probiotics in the development of SLE animal models. Besides, we follow through literature to survey whether probiotics supplements can be an adjuvant therapy for comprehensive treatment of SLE. Research has indicated that intake of probiotics alters the composition of the gut microbiome, contributing to prevent the progression of SLE. Adjustment of the gut microbiome through probiotics supplementation seems to alleviate SLE symptoms and their cardiovascular and renal complications in animal models, marking this treatment as a potentially novel approach.